(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2024)
The research aimed to build a proposed vision for achieving a healthy school environment in the basic education stage in light of the results of the Education Transformation Summit (2022) by identifying the proposed standards and indicators to achieving a healthy school environment in the basic education stage. The research relied on the descriptive analytical approach, and the research tools were a questionnaire directed To experts specialized in this field according to the Delphi method, and the research sample consisted of (15) experts, The results showed that the indicators for achieving a healthy school environment in the basic education stage in light of the Education Transformation Summit (2022) were high, as the percentage of the arithmetic average for the degree of approval and verification was higher than (90%) in the majority of indicators, and the healthy physical school environment was represented by the presence of a school building. It includes a number of classrooms equipped with comfortable, appropriate and flexible furniture, The healthy physical school environment was represented by the presence of a school building that included a number of classrooms equipped with comfortable, appropriate and flexible furniture, large courtyards and courtyards for practicing various types of leisure and recreational activities. It was also represented by the presence of a healthy physical environment. The school has qualified cadres to take care of the school environment and are qualified to implement educational activities that stimulate creativity and innovation.